Rebate Rules in Reward-Based Crowdfunding: Introducing the Bid-Cap Rule - Fabian Gerstmeier; Yigit Oezcelik; Michel Tolksdorf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We study the efficacy of rebate rules in reward-based crowdfunding, where a project is only realized when a funding goal is met, and only those who pledge at least a reservation price receive a reward from the project. We propose and experimentally test two rebate rules against the customary all-or-nothing model. Firstly, we adapt the proportional rebate rule from threshold public good games to our reward-based setting. Secondly, we develop the novel bid-cap rule. Here, pledges must only be paid up to a cap, which is determined ex-post such that the provision point is exactly met. Theoretically, the bid-cap rule induces weakly less variance in payments compared with the proportional rebate rule. In our experiment, we find that both rebate rules induce higher pledges and increase the project realization rate in comparison to the all-or-nothing model. Further, we can confirm that the variance of payments is lower under the bid-cap rule compared with the proportional rebate rule.
Keywords: C72; C92; H41; 330; crowdfunding; laboratory experiment; provision point mechanism; rebates